The Effect of Magnetized Water on the Absorption of Cadmium Using Synthetic Effluents by Lantana camara Species - Elahe Jafari Hafshajani; Mehran Hoodaji; Faezeh Ghanati; Yaghoob Hosseini; Vali Alipour (Shiraz University of Medical Sciences, 2022)
Background: Magnetization of water, as a factor that stimulates the other factors related to plant growth, is an affective physical solution on plant resistance and yield.Methods: In this case-control research, the effect of magnetized water on cadmium removal by Lantana camara was investigated. An experiment with completely randomized-block design was done to irrigate the plant pots using 3 levels of water treatment (W1: magnetic, W2: semi magnetized and W3 non-magnetized:) and 4 levels of cadmium 0, 0.5, 1, and 2 mg/L with 3 replications.Results: The results showed that the interaction effects of cadmium levels and irrigation water treatment on soil, shoot, and root cadmium content were significant. The amount of soil cadmium decreased by 39.49 percent by increasing the concentration of metal (2 mg/L) in irrigation water under the influence of magnetized water treatment. Evaluation of cadmium accumulation, adsorption index and transfer factor showed that the highest amount of them in the treatment of 2 mg / l cadmium in the surface of magnetized water was equal to 0.836, 0.034, and 1.654 respectively. The lowest shoot and root cadmium under the influence of magnetic water treatment was 0.559 and 0.303 (mg Kg-1), respectively, which was significant compared to non-magnetized water treatment. The enzyme activity of CAT (Catalase), SOD (superoxide dismutase), POD (peroxidase), phenol, phenoloid, and anthocyanin was increased by applying magnetic water treatment.Conclusion: Magnetized water by increasing the cadmium absorption by plants and stimulating the plant antioxidants had a significant effect on the absorption and transport of cadmium and increased the efficiency of refining plants by Lantana camara plant.